Learning from the actors and roles in coastal management collaboration to increase the fisherman life - Dewi Casmiwati; Wildan Taufik Raharja; Suprayitno Paendri Dayu; Aisiah Cici Faridah (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
The study starts from the problems in collaboration of coastal management and the various efforts have not been able to improve the welfare of fishermen optimally. This study aims to analyse the actors and their roles in coastal management collaboration in Gisik Cemandi, Indonesia. The type of research is qualitative research with a case study in Gisik Cemandi with aims to reveal phenomena according to the setting and reality. The data used are in the form of primary data and secondary data. The informants consist of Village Head and officials, heads of Village Community, stakeholders and fishermen. The data analysis technique uses thematic analysis techniques, namely through determining themes, data classification, data interpretation and data analysis based on themes. This study found that the actors and their roles in coastal management collaboration are varies. The actors consist of private sectors, universities, government institution. Private sectors provide training, public goods that are needed by fishermen, universities are doing education and training for small enterprises, preserving their sustainable and clean environment, free medical treatment, and increasing the public service quality. Government institution was giving education, training, providing fishing tools and information, guarding the beach security. The private sector and university did all the programs based on trust and community based coastal management, whilst the government collaborate based on formal regulations. The impact of the collaboration can improve fisherman’s skill, fishing livelihood, fish processing product and in social, the fisherman can increase their participation in organization. The challenge of collaboration comes from its continuity. Most of the programs were done in certain time and temporary. Only the programs are coming from government that is continue, so this study recommends to enhance sustainability in collaboration for all actors.